Impact of Cluster Thinning on Wine Grape Yield and Fruit Composition: A Review and Meta-Analysis - Joshua VanderWeide; Esmaeil Nasrollahiazar; Steve Schultze; Paolo Sabbatini; Simone Diego Castellarin (Australian Journal of Grape and Wine Research)
For wine grape producers, achieving an optimal balance between vegetative and reproductive growth is a key factor in producing high quality fruit and meeting production quotas. This balance is often measured as the leaf-area-to-yield ratio. To increase this ratio, producers often use “cluster thinning” (CT), a management practice involving a selective removal of grape clusters from vines. Despite this, no consensus has been established regarding the optimal CT timing and severity for consistently improving fruit composition. The objective of this work was to identify whether CT “timing” (bloom, pea-size, lag phase, and veraison) or “severity” (15–35%, 36–55%, and 56–75%) influences yield and fruit composition. To achieve this objective, a meta-analysis of 160 publications on CT in grape was reduced to 78 studies via 10 data curation steps. We reported the influence of CT timing and severity on yield and fruit composition, as well as their impact on the yield-fruit composition tradeoff. First, CT timing showed little influence on fruit composition, which provides producers with greater flexibility when using this practice. Second, CT severity was impactful on improving fruit composition (TSS and pH); only the moderate range (36–55%) was effective. In conclusion, wine grape composition is more influenced by CT severity than timing. This work has important implications for grape producers and their approach to improving grape composition.